The right to freedom of opinion and expression - Ligabo, Amebyi (Nations Unies, 2006)
On 3 February 2006, the Special Rapporteur, together with the Independent Expert on Minority Issues, the Special Rapporteur on contemporary forms of racism, racial discrimination, xenophobia and related intolerance, and the Special Rapporteur on the situation of human rights and fundamental freedoms of indigenous sent a letter of allegation concerning information received regarding discrimination toward Berbers, particularly on the existence of discriminatory legislations toward the Berber culture and identity, such as the law number 24 of the year 1369 w.r. (1991). Reportedly, the said laws prevent people from using any other language than Arabic in the country and also forbid literature and writings which is not in Arabic, and therefore, the use of the Berber language. It is also alleged that it is forbidden to use names of Berber origin to name children. It has been also alleged that the Libyan government deliberately withholds the development of regions with Berber communities. As an example, the only hospital in the region of Zouara, which was closed in the 1980’s, has not been reopened and that there is no hospital in the region. Similarly, it has been alleged that the water projects in the country have deliberately excluded the regions of Nefoussa and Zouara. The information also alledged that the Libyan education system and school books do not take into account the Berber component in Libya’s geography, history and culture. Allegations also report the harassment and ill-treatment of persons working for the defence of the Berber community, culture and identity.
Keywords: Vie politique – Djebel Nefousa

Examen des rapports présentés par les États parties conformément aux articles 16 et 17 du pacte : Jamahiriya arabe libyenne : Observations finales du comité des droits économiques, sociaux et culturels (Conseil économique et social, 2006)
Keywords: Vie politique – Djebel Nefousa